Halloumi cheese : the product and its characteristics - Robinson, Richard; Papademas, Photis (My University, 1998)
Halloumi, the traditional cheese of Cyprus, is extremely popular in the Middle East and the Mediterranean regions of Europe and in recent years exports from Cyprus have risen. The basic cheesemaking process places halloumi in the family of white brined cheeses, but some of its characteristics are quite unique. This paper reviews the studies that have been carried out on the chemical composition, manufacturing procedure(s), sensory quality and storage of halloumi, and considers some proposed developments, such as the use of reconstituted milk powders or homogenized milk
Keywords: Cheese; Cheesemaking; Milk; Homogenized milk